Efficacy of a new treatment algorithm for capsulitis of the fingers in rock climbers - Schöffl, V. R.; Lutter, C.; Lang, H.-C.; Perl, M.; Moser, O.; Simon, M. (Frontiers in Sports and Active Living, 2025)
Background: Although finger joint capsulitis has been described among the most frequent injuries in climbers, no clinical studies on treatment strategies and outcomes are available.